Experimental investigations on the rheological properties of the proposed 3D printing mortar - Thi Loan Pham; Xiao Jian Zhuang; Thi Hoai Thu Nguyen; Phan Anh Nguyen; Duy Thanh Trinh (Vietnam Journal of Science, Technology and Engineering, 2022)
In order to explore the full potential that 3D technology can bring to the construction industry, considerable amounts of research have been carried out all over the world. However, compared to traditional construction, research related to the application of 3D printing in the construction industry is still in its infancy. Publications related to applying 3D printers in the construction fi eld has become a hot trend in recent decades. Even after nearly three decades of global exploration into numerous projects, the complete potential of 3D printing technology in the construction industry remains unrealized. Numerous challenges impede the effective application of 3D printing in construction, with the formulation of the concrete mixture being a critical factor. This study specifically addresses mix proportion design approaches and tests, focusing on assessing the rheological properties of fresh mortar. In consideration of their practicality and relevance in construction, materials like cement, fly ash, and natural sand were chosen for the mix proportion analysis. The study employed slump-flow tests, V-funnel tests, and buildability tests to evaluate the properties of the fresh mortar. This initial exploration into mixture proportion and the methodology for assessing rheological properties in 3D printing mortar serves as a valuable reference and guide, laying the groundwork for the development of 3D printing technology in Vietnam.